Phenology, Seed Biology and Seedling Survival and Growth of Aquilaria Malaccensis: a Highly Exploited and Red Listed Tree Species of North East India - Saikia, P.; Khan, M. L. (Indian Forester, 2012)
Life history of Aquilaria malaccensis including its phenology, seed production, size, weight, moisture content, viability, germination, seedling growth and survival was studied. It was found that 70.5% fruits were two seeded leaving the rests as one seeded. Seed production was found variable among different trees and individual tree can produce 5,092 to 16,660 seeds per year. Most of the seeds were having weight range between 0.014 and 0.251 gm and diameter between 3.86 mm and 5.50 mm. Tetrazolium test of freshly collected seeds showed 100% viability which decreased with the increase in storage duration. Germination started after 7 days of sowing and continues up to 45 days. Both the mean seasonal survival rate and growth rate of seedlings in terms of collar diameter was highest in 50% irradiance level followed by 25% and 75% irradiance level and survival was maximum during February to April (98% ± 0.88) and lowest during May to July (90% ± 4.53) but, growth was highest during May to July (34.47% ± 5.02) and lowest during November to January (20.56% ± 4.38) in all the three irradiance levels of the mist house. Findings of the present report may be helpful in developing protocols for large scale production of planting stocks and proper management of the species with immense economic importance with extinction risk.